An Evaluation of Extended Incubation Time with Blind Subculture of Blood Cultures in Patients with Suspect Endocarditis - Kevin R Forward (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: In a small proportion of patients, bacterial endocarditis is due to organisms that grow slowly and may not be recovered in conventional blood cultures incubated for five days. This has led to recommendations for prolonged incubation and routine subculture of negative cultures.